Hazardous drinking and clinical correlates among suicidal patients receiving psychiatric inpatient care at military medical settings. (March 2020) - Luk, Jeremy W.; LaCroix, Jessica M.; Thompson, Matthew F.; Darmour, Charles; Perera, Kanchana U.; Goldston, David; Soumoff, Alyssa; Weaver, Jennifer; Ghahramanlou-Holloway, Marjan
Highlights: Data were collected from a unique sample of military psychiatric inpatients. In this clinical sample, 28.9% of participants reported hazardous drinking. Hazardous drinking was associated with a diagnosis of Substance Use Disorder. Hazardous drinking was associated with a history of actual, but not interrupted or aborted, suicide attempt(s). Link between hazardous drinking and single attempt history remained after controlling for covariates. Abstract: Background: To describe prevalence and identify clinical correlates of hazardous drinking among suicidal inpatients at military medical settings. Method: Data were drawn from the baseline assessment of a multisite randomized controlled trial of Post-Admission Cognitive Therapy (PACT). Participants were military Service members or adult beneficiaries ( N = 218) who were admitted to inpatient care following a suicide-related crisis. Hazardous alcohol use in the past year was assessed using the Alcohol Use Disorder Identification Test (AUDIT). Results: The average AUDIT score was 6.78 ( SD = 7.87), with 28.9% reporting hazardous drinking (scored ≥8 on the AUDIT). Hazardous drinkers were more likely than nonhazardous drinkers to meet diagnosis of Substance Use Disorder (SUD; Odds Ratio [OR] = 5.96, 95% confidence intervals [CI] = 2.13, 16.71). Hazardous drinking was neither associated with measures of suicide ideation nor aborted or interrupted suicide attempt. However, hazardous drinkers had greater risk of having both single (RRR [Relative Risk Ratio] = 2.55, 95% CI = 1.18, 5.50) and multiple actual suicide attempts (RRR = 2.38, 95% CI = 1.06, 5.32) than nonhazardous drinkers. The association between hazardous drinking and single (but not multiple) actual suicide attempt remained significant after controlling for gender, depressive symptoms, hopelessness, Post-Traumatic Stress Disorder, and SUD (adjusted RRR = 2.48, 95% CI = 1.09, 5.65). Conclusions: A history of actual suicide attempt is associated with hazardous alcohol use among suicidal psychiatric inpatients. Assessment of drinking and drug use may inform case conceptualization and treatment of suicide-related behaviors in psychiatric inpatient settings.